Avaliação hemorreológica e produção de citocinas em cães naturalmente infectados por Anaplasmataceae - Cardoso, Saulo Pereira (2018)
In this work naturally infected dogs with Anaplasmataceae shows decrease in blood viscosity and IFN-γ serum concentration as the cytokine responsible for rheological change, as well as one of the causes of erythrocyte reduction. Fresh blood samples was measured by the Modular Compact Rheometer – MCR 102 [Anton Paar® GmbH, Ostfildern, Germany] to obatin rheometric data and the graphs were obtained using Rheoplus software. Blood count data were obtained by automatic analysis using Celltac [Nihon Khoden®]. Diagnostic confirmation was obtained by molecular PCR technique to determine the groups of not infected and infected by Anaplasmataceae. Serum cytokines were dosed by flow cytometry (FACScalibur BD®) using BD® Biosciences Cytometric Bead Array (CBA) Human Th1 / Th2 / Th17 Cytokine kits. The results showed a correlation between blood viscosity (p <0.05, r = 0.73) and shear rate (p <0.05; r = -0.676) with IFN-γ in the group of infected dogs that presented anemia, as well as correlations of shear rate with erythrocytes (p <0.05; r = -0.88). In addition, infected animals demonstrated a decrease on blood viscosity. Thus, IFN-γ appears to play an important role in the immunomodulation of the rheological behavior of naturally infected dogs with Anaplasmataceae.